Chapter 6 Negotiating the Arabic and English Space in UAE Higher Education The Ownership of English in the English-Medium Instruction Context - Zoghbor, Wafa S. (Taylor & Francis, 2023)
The United Arab Emirates puts tremendous effort into protecting the Arabic language and reinforcing its position as the language of the country's constitution and national identity. The country's higher education system is built on English-medium instruction, which, alongside the worldwide adherence to native-like norms that accompanies English as a global language, appears to reduce the opportunities for Arab students to take ownership of English. This chapter focuses on the negotiable space between Arabic and English in a United Arab Emirates English-medium instruction higher education context. Data were triangulated from self-reflections by thirty Emirati students (20 females and 10 males) and interviews with four faculty members of maths and information technology who taught through English. The findings show that while English-medium instruction is considered a form of multilingual education, Arabic was believed to have a positive impact on the students' control over their university courses. The chapter provides implications for how multiple competencies can help Arab students exercise ownership of English, reduce their linguistic and cultural insecurities, and retain their identity while learning in an English-medium instruction context.